The Practice of Inclusion and the Training Needs of Inclusive Education Teachers in Relation to Geographical Location in Lagos State - Manuel, Mojisola Nkechi; Gladys, Emiola Adetoun (NIU Journal of Social Sciences, 2019)
Inclusive education demands the equal rights of both special needs and regular learners in the general classroom irrespective of disabilities and geographical location. The implementation of inclusion following the UNESCO’S standard requires a huge commitment of human and material resources as well as adequate teacher preparation. It was observed that Lagos State Government embarked on the implementation of inclusion in the State since 2003. In view of this, the study investigates the practice of inclusion with special reference to teacher’s status, training, practice and teacher’s ratings of the performance of special needs learners in the inclusive units situated in a defined geographical location, Lagos State. The sample consisted of all the eighty three (83) teachers in the 29 inclusive units in the geographical area known as Lagos State. Three (3) research questions and two hypotheses were formulated to guide the study. Descriptive survey research design was used. Data was analyzed using descriptive statistics while the hypotheses were tested using chi-square at 0.05 level of significance. Some notable findings are that, not all the teachers in the inclusive units were beneficiaries of the inclusive training conducted twice so far. Learners with hearing impairment topped the rating list by trained and untrained teachers. Similarly, trained teachers attested that there was a marked difference in their classroom delivery as a result of the training. Against the aforementioned, the study recommends that the inclusive units in all geographical locations in the State should be majorly manned by trained regular teachers and that government should invest in more support to aid the learning of other learners. Key words: Geographical location, inclusive education, special needs, trained teachers, teacher’s status